A novel low-temperature solid-state route for nanostructured cubic garnet Li7La3Zr2O12 and its application to Li-ion battery. Issue 67 (30th June 2016) - Kumar, P. Jeevan; Nishimura, K.; Senna, M.; Düvel, A.; Heitjans, P.; Kawaguchi, T.; Sakamoto, N.; Wakiya, N.; Suzuki, H.
Abstract : Garnet Li7 La3 Zr2 O12 nanoparticles with 1 mass% Al were prepared via a solid-state route at 750 °C within 3 h. A model cell sandwiched by Li and LiCoO2 exhibited initial discharge capacity of 64 μA h cm −2 μm −1, being 93% of LiCoO2 theoretical value. Abstract : We present a novel approach to the solid-state synthesis of garnet-type cubic Li7 La3 Zr2 O12 (c-LLZO) nanostructured particles with 1.0 mass% Al at 750 °C within 3 h. In contrast to conventional solid-state processes, a highly reactive precursor was prepared in two steps: (i) by homogenizing the stoichiometric mixture without Li, and (ii) subsequent addition of Li in the form of an ethanolic solution of lithium acetate. The actual composition determined by ICP analysis was Li6.61 La3 Zr2 Al0.13 O11.98 . Sintering these nanoparticles at 1100 °C for 3 h in air after cold isostatic pressing brought a dense ceramic pellet with a relative density of 90.5%. The corresponding ionic conductivity with Au electrodes was 1.6 × 10 −4 S cm −1 at room temperature. To study its electrochemical behavior as an electrolyte, a model cell of Li//(1 M LiPF6 + c-LLZO)//LiCoO2 configuration was constructed. Cyclic voltammetry of the cell delivered one set of redox couple with narrow voltage separation (15 mV) with a Li + diffusion coefficient at room temperature of about 2 × 10 −11 cm 2 s −1 at the interface between LiCoO2 and 1 M LiPF6 + c-LLZO. The cell received an average discharge capacity of 64.4, 60.3, 56.1, 51.9 and 46.9 μA h cm −2 μm −1 at discharge rates 0.5C, 1C, 2C, 4C and 6C, respectively. The cell exhibited complete oxidation and reduction reactions with an average initial discharge capacity of about 64 μA h cm −2 μm −1, which is 92.7% of LiCoO2 theoretical value. These observations indicate the applicability of the present c-LLZO as an electrolyte for a solid-state Li-ion battery.